PHENOMENOLOGICAL STUDY: THE DYNAMICS OF LIVED EXPERIENCES AND QUALITY OF LIFE CHANGES AMONG CANCER SURVIVORS IN THE KUPANG CANCER SUPPORT COMMUNITY - Maria Magdalena Dwi Wahyuni; Adzhar Al-Aziz; Ergayona Purwaningsih Kensli Fernandez; Martina Wea; Desinta Bolang Sir (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Cancer survivors experience various physical, psychological, social, and functional changes throughout diagnosis, treatment, and recovery. Understanding cancer survivors' lived experiences is essential for describing changes in their perceived quality of life. This study aimed to explore these experiences from the time of the initial cancer diagnosis throughout the entire treatment process. The data were analyzed using thematic analysis based on the participants lived experiences. Data were collected through in-depth interviews with five cancer survivors residing at the Cancer Patient Shelter of the Cancer Support Community in Kupang City. Participants were selected using purposive sampling. The findings revealed that all participants experienced emotional responses, including fear, anxiety, stress, and uncertainty, following their cancer diagnosis. Participants also reported physical changes, such as pain, fatigue, weight loss, and limitations in performing daily activities. Treatments, including surgery, chemotherapy, radiotherapy, and regular medical follow-up, contributed to improvements in participants' health despite persistent treatment-related side effects. Family support emerged as the primary source of motivation, enabling participants to continue their treatment. Furthermore, the experience of living with cancer encouraged healthier lifestyle changes, increased awareness of the importance of early detection, and strengthened participants' ability to adapt to their illness. The lived experiences of cancer survivors demonstrate that quality of life is influenced by physical condition, psychological responses, social support, treatment adherence, and lifestyle changes. Continuous support from family members and healthcare providers is essential for helping cancer survivors maintain their quality of life throughout the treatment journey.